Urdu Diaspora in Canada: Unveiling the Transnational Experiences through Jawaid Danish’s Hijarat Ke Tamashey - Chapparban, Sajaudeen Nijamodeen; Shaheen, Shugufta (Muslim English Literature, 2025)
Urdu Diaspora can be defined as the socio-cultural formation of the Urdu-speaking community in transnational spaces, which has migrated chiefly from the Urdu-speaking regions in India and Pakistan to various global destinations, including the EU, the Americas, Australia, Canada, the Caribbean, African countries, and Gulf nations. The present paper endeavours to provide a concise overview of the global Urdu diaspora with special reference to the South Asian and specifically Indian Urdu-speaking Diaspora community in Canada. It also intends to describe the fundamental characteristics of the Urdu diaspora in relation to the other classical patterns of global diasporas. It applies literary analysis to the transnational experiences of the South Asians as depicted in the works of Indo-Canadian writer and playwright Jawaid Danish's literary work – cum – performance, Hijrat Ke Tamashey (Plays of Migrations). It is a collection of various plays based on the lives of immigrants in Canada. Danish is also popular for his solo play “Dastan Hijraton Ki” (Story of Migration). This story is a Dastan/goi, a traditional form of Urdu storytelling. The present qualitative research seeks to shed light on the multifaceted aspects of lived experiences, memories, the anguish of displacement, notions of belonging, and the challenges encountered by Indian and Pakistani Urdu-speaking communities during the transition into a different socio-cultural setting.  It aims to draw parallels between the American dream and the Canadian dream, as well as the hardships associated with both. Furthermore, this study seeks to underscore the pivotal role played by the diaspora in preserving and promoting the Urdu language, literature, identity, and cultural heritage in transnational space concerning Canada.